2012
DOI: 10.1089/jpm.2011.0310
|View full text |Cite
|
Sign up to set email alerts
|

Association of Age, Gender, and Race with Intensity of End-of-Life Care for Medicare Beneficiaries with Cancer

Abstract: Seniors dying with poor-prognosis cancer experience high-intensity care with rates varying by age, gender, and race.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
120
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 36 publications
21
120
3
Order By: Relevance
“…For instance, women had lower odds of hospitalization and receipt of aggressive care in several EOL care studies, whereas individuals who reported a black race/ethnicity, a lower SES, and comorbidities had higher odds. [28][29][30][31][32] Our finding that increased age was associated with lower rehospitalization rates was consistent with results of a Canadian study on EOL care for advanced pancreatic cancer 33 and a US study of Medicare beneficiaries with poor-prognosis cancers in the last 6 months of life. 28 However, this finding was inconsistent with one study, in which increased age was associated with more aggressive EOL care.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…For instance, women had lower odds of hospitalization and receipt of aggressive care in several EOL care studies, whereas individuals who reported a black race/ethnicity, a lower SES, and comorbidities had higher odds. [28][29][30][31][32] Our finding that increased age was associated with lower rehospitalization rates was consistent with results of a Canadian study on EOL care for advanced pancreatic cancer 33 and a US study of Medicare beneficiaries with poor-prognosis cancers in the last 6 months of life. 28 However, this finding was inconsistent with one study, in which increased age was associated with more aggressive EOL care.…”
Section: Discussionsupporting
confidence: 82%
“…[28][29][30][31][32] Our finding that increased age was associated with lower rehospitalization rates was consistent with results of a Canadian study on EOL care for advanced pancreatic cancer 33 and a US study of Medicare beneficiaries with poor-prognosis cancers in the last 6 months of life. 28 However, this finding was inconsistent with one study, in which increased age was associated with more aggressive EOL care. 31 Our multistate modeling approach fully accounted for time during which individuals were not at risk for hospitalization (because of either death or time spent in the hospital).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…8,9 However, rates have been slowly rising over the last decade, and 5% to 22% of all patients with advanced cancer receive chemotherapy within 2 weeks of death. [2][3][4][10][11][12][13][14][15][16][17][18] Previous research on chemotherapy administration at EOL has primarily focused on predictors and outcomes. Although these studies have helped to identify the scope of the problem, few have examined when and how oncologists discontinue chemotherapy, including how the timing influences patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…16 In comparison, in the final 6 months of their life, 55% of patients with cancer enrolled in hospice, and only 15% enroll within 3 days of their death. 17 We hypothesize that palliative care has the potential to improve clinical outcomes for patients living with HF by improving pain and other symptom control, clarifying goals of care, and guiding treatment decisions to meet those goals.…”
Section: Introductionmentioning
confidence: 99%